Upaya Meningkatkan Daya Tahan Cardiovascular Melalui Pendekatan Bermain dalam Pembelajaran Pendidikan Jasmani - Muslim Muslim; Aco Tang (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction; Physical education is a learning method created to improve the physical fitness of students. Objektif; knowing the physical education learning model by applying a play approach can increase students' cardiovascular endurance. Method; The research used is a sports class action research in which there is repeated reflection in the form of planning, action, observation, observation in stages. Data were collected by observation during the teaching and learning process. Qualitative data is first converted into quantitative data which is analyzed descriptively. Results; The average score of students' cardiovascular endurance before applying the learning model using the play approach method was 13.81 for boys and 18.01 for girls, then increased after the application of the learning model with the playful approach to 13.56 for boys and 17.84 for women in the first cycle and 13.08 for men, 17.67 for women in the second cycle. An increase in cardiovascular endurance. Conclusion; that physical education learning model by applying a play approach can increase students' cardiovascular endurance